Connecting catch profiles with efficiency: An application to the beam trawl fishery in the Northern Adriatic Sea - Ceccacci, Alberto; Russo, Elisabetta; Mulazzani, Luca; Malorgio, Giulio (Regional studies in marine science, 2024)
Estimation of technical efficiency in fisheries is most commonly finalized at comparing the conversion from inputs (e.g. time at sea, fuel consumption) to production (i.e. landed fish) among vessels or gears. In this paper we adopt a novel approach focusing on the efficiency of fishing trips characterized by different catch composition within the same fleet. In particular, the case study under analysis is represented by the beam trawl (“rapido”) fishery of Chioggia (Adriatic Sea, GSA 17), which has been subject to increasing technical and effort limitations in recent years due to its severe impacts on the marine ecosystem. The methodological strategy first involves a cluster analysis of catch profiles to identify homogeneous groups of fishing trips, which are subsequently compared in terms of economic performance based on the efficiency scores from stochastic frontier analysis. By including also an estimation of Greenhouse Gas emissions per trip, the results from our study can be used to inform future management interventions that aim at improving the overall efficiency of the fishery while reducing its carbon footprint and the pressure on the most relevant target species.